Fluid mechanics and the SPH method theory and applications - Violeau, Damien (Oxford : Oxford University Press, 2012)
This text presents the SPH method for fluid modelling from a theoretical and applied viewpoint. It explains the foundations of the method, from physical principles, and will help researchers, students, and engineers to understand how the method should be used and why it works well.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Fluid mechanics -- Mathematical models; Fluid mechanics -- Computer simulation; Hydrodynamics -- Mathematical models; Hydrodynamics -- Computer simulation